Phylogeny and toxicological assessments of two Porthidium lansbergii lansbergii morphotypes from the caribbean region of Colombia. (August 2019) - De arco-Rodríguez, Beatriz; Montealegre-Sánchez, Leonel; Solano-Redondo, Luis; Castro-Herrera, Fernando; Ortega, José Guillermo; Castillo, Andrés; Vargas-Zapata, Carmiña; Jiménez-Charris, Eliécer
Abstract: After a snakebite accident, species identification is of vital importance. However, the existence of intraspecific differences in the body coloration patterns of venomous snakes can generate confusion and delay a convenient and effective treatment. This is the situation for Porthidium lansbergii lansbergii from Colombia, for which two distinctive color morphs occur, and the relationship of these morphs with venom toxicity is unknown. Therefore, venom samples from specimens of these two morphs were collected from the Colombian Caribbean region, and their protein profiles compared. Likewise, their venom functional activities were evaluated in vitro and in vivo in BALB/C mice. Additionally, using sequences of the mitochondrial cytochrome b (Cyt-b) gene, the relationship between these Colombian P. lansbergii lansbergii morphotypes was investigated, and their phylogenetic positions were determined for the first time using Bayesian inference. Despite the noticeable coloration divergence between the individuals analyzed, similar protein profiles of their venoms were observed. Additionally, neither their lethality nor biochemical activities were notably different. In general, both venoms were highly proteolytic, lacked a coagulant effect in vitro, and extended the clotting time due to the action of venom components, such as disintegrins and proteases, that induce defibrination. These results agreed with the result of our phylogenetic analysis, suggesting that the two chromatic morphs do not represent isolated populations. The phylogenetic analyses also supported the currently recognized P. lansbergii lansbergii subspecies as a monophyletic complex. In conclusion, the results of this investigation suggest similar clinical manifestations regardless of body coloration after a P. lansbergii lansbergii envenomation, and pools can therefore be used for antivenom development, medical treatments, and further research efforts. Highlights: First toxinological comparison of venoms from two Porthidium lansbergii lansbergii morphotypes from Colombia. Venoms from both P. lansbergii lansbergii two–color morphs are remarkably conserved and envenoming clinical manifestations were mostly the same. A phylogenetic analysis that included for the first time four new mitochondrial Cyt–b gene sequences of P. lansbergii lansbergii. There were not enough differences between Cyt–b gene sequences as to consider both P. lansbergii lansbergii morphotypes as different populations. The phylogenetic analysis supported the currently recognized P. lansbergii subspecies as a monophyletic complex.